Play: Serious Business - Herbert, Susan (Daily Express, 2005)
This article addresses the importance of play in learning, thinking, and development, and seeks to show that the serious business of teaching is not incompatible with the serious business of play. It provides examples of students' play serving as a resource to make learning meaningful and fun
Keywords: Play; Learning outcomes